Silver - Franck, Irene M; Brownstone, David M (Danbury, Conn Grolier, 2003)
Provides information about silver and its importance in everyday life
Includes bibliographical references (p. 31) and index
Hurg
5
Keywords: Silver -- Juvenile literature; Silver